Human Melanoma-Derived Extracellular Vesicles Regulate Dendritic Cell Maturation - Maus, Rachel L. G.; Jakub, James W.; Nevala, Wendy K.; Christensen, Trace A.; Noble-Orcutt, Klara; Sachs, Zohar; Hieken, Tina J.; Markovic, Svetomir N. (Frontiers in Immunology, 2017)
Evolution of melanoma from a primary tumor to widespread metastasis is crucially dependent on lymphatic spread. The mechanisms regulating the initial step in metastatic dissemination via regional lymph nodes remain largely unknown however evidence supporting the establishment of a pre-metastatic niche is evolving. We have previously described a dysfunctional immune profile including reduced expression of DC maturation markers in the first node draining from the primary tumor, the sentinel lymph node (SLN). Importantly, this phenotype is present prior to evidence of nodal metastasis. Herein, we evaluate melanoma-derived extracellular vesicles (EVs) as potential mediators of the pre-metastatic niche through cargo-specific polarization of dendritic cells (DCs). Matured in vitro in the presence of melanoma EVs, DCs show significantly impaired expression of co-stimulatory markers CD83 and CD86 compared to liposome treated DCs as well as decreased expression of Th1 polarizing cytokines Flt3L and IL15 and migration chemokines MIP1α and MIP1β. Profiling of melanoma EV cargo identified shared proteomic and RNA signatures including S100A8 and S100A9 protein cargo which in vitro compromised DC maturation similar to melanoma EVs. Early evidence demonstrates similar EVs can be isolated from human afferent lymphatic fluid ex vivo. Taken together, here we propose melanoma EV cargo as a mechanism by which DC maturation is compromised warranting further study to consider this as a potential mechanism enabled by the primary tumor to establish the pre-metastatic niche in tumor-draining SLNs of patients.